The Impact of the White Label Model in the Global Market on the Local Fashion Industry - Zulfa Nailin Najah; Fandy Ardiansyah; Muhammad Naufal Mahbub; Arifanny Cindy S; Arga Christian Sitohang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the impact of the white label production model within the global market and its implications for the development and sustainability of local fashion industries. Drawing on theoretical perspectives and empirical findings, the research reveals that white label systems provide significant advantages for emerging brands by reducing capital barriers, accelerating production processes, and enabling rapid market entry. The increasing digitalization of global supply chains further strengthens the accessibility of foreign manufacturers, allowing local brands to source ready-made products efficiently. However, the study also identifies substantial challenges, including product homogenization, declining brand differentiation, dependence on overseas manufacturers, and weakened competitiveness of domestic textile and garment sectors. Additionally, the widespread use of generic designs contributes to the erosion of cultural identity within local fashion. Overall, the findings indicate that while the white label model offers strategic opportunities for brand growth, it simultaneously poses long-term risks to industrial resilience and creative sustainability. The study highlights the need for balanced strategies that integrate white label advantages with efforts to strengthen originality, cultural expression, and local manufacturing capacity.